Method for producing regenerated water-absorbing resin composition and regenerated water-absorbing resin composition

JP2025025613APending Publication Date: 2025-02-21NIPPON SHOKUBAI CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023130512
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0023】 本発明によって、過度の精製や過剰な精製剤も必要とせずに、着色や臭気、残存モノマーが改善できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025025613000001_ABST
    Figure 2025025613000001_ABST
Patent Text Reader

Abstract

To provide a method for obtaining, from used water-absorbing resin, a regenerated water-absorbing resin composition that is less degraded and has less coloring and fewer impurities or residual monomers, without excessively consuming resources during recycling.SOLUTION: A method for producing a regenerated water-absorbing resin composition using used water-absorbing resin or its solubilized material as part or all of raw materials comprises: performing azeotropic dehydration (first drying) of a water-containing gel-like crosslinked polymer in the presence of a surfactant or a polymer dispersant in a hydrophobic organic solvent so as to obtain a water-containing gel-like crosslinked polymer with a water content from 5 mass% to 50 mass% inclusive; separating the hydrophobic organic solvent and the water-containing gel-like crosslinked polymer (semi-dried gel) by filtration or evaporation to dryness; and drying by heating under stirring (second drying) to obtain a dried polymer with a water content from 1 mass% to 20 mass% inclusive.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a recycled water-absorbent resin composition using a used water-absorbent resin or a solubilized product thereof (a decomposition product of a water-absorbent resin) as a raw material, and to a recycled water-absorbent resin composition. [Background technology]

[0002] In recent years, water-absorbent resins have been widely used as constituent materials for absorbent articles such as paper diapers, sanitary napkins, incontinence pads, absorbent sheets, cat litter, etc., from the viewpoint of absorbing body fluids. Although absorbent articles, which are the main application of water-absorbent resins, are generally disposable, there has been growing interest in recycling sanitary products such as paper diapers due to the increasing environmental awareness.

[0003] One proposed method for recycling used sanitary products (for example, disposable diapers that have absorbed human waste) involves collecting the used sanitary products, separating them into their component parts such as pulp, nonwoven fabric, adhesive, and water-absorbent resin, and then washing, refining, sterilizing, and bleaching them before recycling.

[0004] Among these components, water-absorbent resins swell by absorbing the cleaning water and sterilizing water in the recycling process, and the urine contained in the cleaning water in the cleaning process, so they need to be washed and dried before they can be reused as products, and it is known that they deteriorate and become discolored due to the heat during drying. For this reason, recycling water-absorbent resins has been technically difficult.

[0005] Conventionally, technology has been proposed to solubilize used water-absorbent resin with a decomposing agent in order to recover pulp, nonwoven fabric, adhesives, etc. from sanitary products. However, since water-absorbent resin is difficult to recycle or separate, it has generally been solubilized to separate the pulp, etc., and then disposed of.

[0006] However, in recent years, a technology has been developed for separating and regenerating used water-absorbent resins for use in absorbent articles, and recycling them into water-absorbent resins or other useful substances (e.g., water-soluble polymers and adhesives).

[0007] As a method for recycling used water-absorbent resin, a method has been proposed in which the used water-absorbent resin is separated from used absorbent articles (particularly sanitary products such as paper diapers), purified, and reused (Patent Documents 1 to 3).

[0008] A recycled water absorbent resin composition obtained from a used water absorbent resin is reused as a water absorbent resin as it is. However, since a performance of a recycled water absorbent resin composition is generally deteriorated in a recycling process, the use of the recycled water absorbent resin composition is actually limited.

[0009] In view of this, as applications of the recycled water absorbent resin composition, which is likely to be accompanied by a decrease in performance due to recycling, methods have been proposed for reducing the amount of raw materials used for the water absorbent resin and restoring the performance of the recycled water absorbent resin composition by using the recycled water absorbent resin composition as a raw material for the water absorbent resin (Patent Document 6) or using a solubilized matter of used water absorbent resin as a raw material for the water absorbent resin (Patent Documents 4, 7 to 11).

[0010] However, in the case of a used water absorbent resin (particularly a water absorbent resin separated from a used sanitary product), since the water absorbent resin absorbs water and swells, it is difficult to control the separation of water-soluble components such as urine, and further, when separating the water absorbent resin, there has been a problem that foreign matter such as pulp or nonwoven fabric is mixed into the separated water absorbent resin due to the stickiness of the water absorbent resin after swelling.

[0011] Foreign matters such as urine components and pulp remaining in a recycled water absorbent resin composition obtained from a used water absorbent resin are likely to cause odor or coloring of the water absorbent resin, an increase in residual monomers, and a decrease in water absorption performance through a production process for the water absorbent resin involving heating.

[0012] That is, although the water-absorbent resin is white, since its main application is paper diapers, a recycled water-absorbent resin composition made from used water-absorbent resin as a raw material has problems of coloring and odor derived from feces and urine, and in order to solve such problems (coloring and odor), bleaching and sterilization have been required in the process of recycling used water-absorbent resin.

[0013] In addition, a method for removing foreign matter such as pulp from a recycled water-absorbent resin composition has been proposed (Patent Document 6), and a technique for adding silica or unused water-absorbent resin in a drying process has also been proposed in order to improve the coloring of a recycled water-absorbent resin composition (Patent Documents 8 and 9).

[0014] However, in the conventional regeneration method, in order to remove impurities (particularly urine components and pulp foreign matter) in the used water absorbent resin, not only does the quality of the regenerated water absorbent resin composition decrease and productivity decrease, but also the regenerated water absorbent resin composition is required to be out of spec or to be subjected to excessive post-treatment (regeneration treatment), and excessive bleaching, sterilization, washing, removal of foreign matter, and use of other additives in recycling the water absorbent resin not only increase the regeneration cost and deteriorate the regenerated water absorbent resin composition, but are also undesirable from the viewpoint of the consumed resources and energy, and from the balance between the regenerated resources and the consumed resources involved in regeneration. In addition, impurities remaining in the used water absorbent resin and chemicals (bactericides, decomposers, etc.) used in the refining process thereof inhibit the polymerization of the water absorbent resin, and are likely to cause an increase in the residual monomers of the water absorbent resin and a decrease in its performance.

[0015] Many recycling methods for used water absorbent resins have been proposed, including those in Patent Documents 1 to 11, but the regeneration process of used water absorbent resins has problems such as contamination with foreign matter such as pulp, coloring, and odor. There are significant restrictions on using a regenerated water absorbent resin composition as a water absorbent resin, or using used water absorbent resins or their solubilized products as raw materials for water absorbent resins. [Prior art documents] [Patent documents]

[0016] [Patent Document 1] International Publication No. WO2019 / 087485 [Patent Document 2] International Publication No. WO2019 / 151538 [Patent Document 3] International Publication No. WO2021 / 075506 [Patent Document 4] International Publication No. WO2020 / 241025 [Patent Document 5] International Publication No. WO2021 / 205780 [Patent Document 6] International Publication No. WO2021 / 044690 [Patent Document 7] International Publication No. WO2020 / 213298 [Patent Document 8] International Publication No. WO2022 / 080342 [Patent Document 9] International Publication No. WO2022 / 081523 [Patent Document 10] International Publication No. WO2022 / 082163 [Patent Document 11] International Publication No. WO2022 / 082165 Summary of the Invention [Problem to be solved by the invention]

[0017] To provide a method for obtaining a recycled water-absorbent resin composition having little coloring or residual monomers from a used water-absorbent resin without excessive consumption of resources in recycling.

[0018] While various methods for producing a recycled water absorbent resin composition, particularly methods for purifying a used water absorbent resin, have been proposed, such as Patent Documents 1 to 11, the present inventors have solved the above problems (coloration, foreign matter, performance) by not sticking to improvements in purification of conventional recycled water absorbent resin compositions, nor by excessive purification, but by selecting a specific drying method for solving the problems in the drying step of the recycled water absorbent resin composition, which has not been focused on in the present solution, and more preferably by selecting a specific additive in the specific step of the recycled water absorbent resin composition.

[0019] That is, among many proposals for regenerating methods for used water absorbent resins, regenerating reagents, and solubilizing methods for water absorbent resins for recycling, it has been found that one of the causes of coloration is urea present in urine and ammonia, which is a decomposition product thereof, and in the present invention, in the conventional regeneration methods and regeneration using used water absorbent resins as raw materials, the present invention has focused for the first time on a drying step, which has hardly been paid attention to in conventional recycling methods for water absorbent resins, and has solved the present problem. [Means for solving the problem]

[0020] The present inventors have conducted intensive research to solve the above problems. As a result, they have found that, in producing a recycled water absorbent resin composition using a used water absorbent resin or a solubilized product thereof as a part or all of a raw material, one of the causes of coloring is urea present in urine and ammonia, which is a decomposition product thereof, and further found that the above problems can be solved by performing a specific drying, which has led to the completion of the present invention.

[0021] That is, the present invention (first invention) is a method for producing a recycled water absorbent resin composition using a used water absorbent resin or a solubilized product thereof as a part or all of a raw material, and the method includes (A) a drying step of a hydrogel crosslinked polymer derived from a purified used water absorbent resin, or (B) a polymerization step of an unsaturated monomer aqueous solution, and in the drying step of a hydrogel crosslinked polymer obtained by using a purified used water absorbent resin or a solubilized product thereof as a part of a raw material, the hydrogel crosslinked polymer is azeotropically dehydrated (first drying) in a hydrophobic organic solvent in the presence of a surfactant or a polymer dispersant to obtain a hydrogel crosslinked polymer having a water content of 5% by mass or more and 50% by mass or less, and then filtered or evaporated to dryness to separate the hydrophobic organic solvent and the hydrogel crosslinked polymer (semi-dried gel), and further heated and dried (second drying) under stirring to obtain a dried polymer having a water content of 1% by mass or more and 20% by mass or less.

[0022] In addition, as a second invention, there is provided a recycled water-absorbent resin composition using a used water-absorbent resin or a solubilized product thereof as a part or all of a raw material, the recycled water-absorbent resin composition containing a surfactant or a polymer dispersant, containing 1 ppm or more and 1000 ppm or less of a hydrophobic organic solvent, and further containing urea or ammonia. Effect of the Invention

[0023] According to the present invention, coloration, odor and residual monomers can be improved without the need for excessive purification or the use of an excessive purification agent. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is a schematic diagram showing a drying apparatus (a drying pot equipped with stirring blades (lattice blades) used in azeotropic dehydration) according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic diagram showing a drying apparatus (a drying pot equipped with stirring blades (paddle blades) used in azeotropic dehydration) according to one embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic diagram showing a drying device (an agitation dryer (paddle dryer) used in agitation drying) according to one embodiment of the present invention. [Figure 4] FIG. 1 is a schematic diagram showing a drying apparatus (a container rotary dryer with scraping blades used in agitation drying) according to one embodiment of the present invention. [Diagram 5] FIG. 1 is a schematic diagram showing a drying apparatus (a container rotary dryer with a heating tube used in agitation drying) according to one embodiment of the present invention. [Figure 6] FIG. 1 is a schematic diagram showing a drying apparatus (a fluidized bed dryer used in agitation drying) according to one embodiment of the present invention. [Figure 7] FIG. 1 is a schematic diagram showing a ventilation band type dryer. [Figure 8] FIG. 1 is a schematic diagram showing a drum dryer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The present invention (first invention) is a method for producing a recycled water-absorbent resin composition using a used water-absorbent resin or a solubilized product thereof as a part or all of a raw material, and the method includes (A) a drying step of a hydrogel-like crosslinked polymer derived from a purified used water-absorbent resin, or (B) a polymerization step of an unsaturated monomer aqueous solution, and in the drying step of a hydrogel-like crosslinked polymer obtained by using a purified used water-absorbent resin or a solubilized product thereof as a part of a raw material, the hydrogel-like crosslinked polymer is azeotropically dehydrated (first drying) in a hydrophobic organic solvent in the presence of a surfactant or a polymer dispersant to obtain a hydrogel-like crosslinked polymer having a water content of 5% by mass or more and 50% by mass or less, and then the hydrophobic organic solvent is filtered or evaporated to dryness to separate it from the hydrogel-like crosslinked polymer, and further heated and dried (second drying) under stirring to obtain a dried polymer having a water content of 1% by mass or more and 20% by mass or less. This is a method for producing a recycled water-absorbent resin composition.

[0026] Each of the configurations will be described below.

[0027] (1) A hydrous gel-like cross-linked polymer to be dried In the method for producing a recycled water absorbent resin composition of the present invention, the hydrogel crosslinked polymer to be dried (hereinafter, abbreviated as "hydrogel") is (A) Hydrogel derived from used water absorbent resin after purification; (B) A hydrogel obtained by using a purified used water absorbent resin or a solubilized product thereof as a part of a raw material in a production process of a recycled water absorbent resin composition including a polymerization process of an unsaturated monomer aqueous solution; Examples include:

[0028] Here, in the above (A), only the hydrous gel of the used water absorbent resin is dried for the purpose of regenerating the used water absorbent resin. In other words, (A) corresponds to a method for producing a regenerated water absorbent resin composition using the used water absorbent resin or its solubilized product as the entire raw material. On the other hand, the above (B) corresponds to a method for producing a regenerated water absorbent resin composition using the used water absorbent resin or its solubilized product as part of the raw material. In other words, in (B), a mixture of the used water absorbent resin or its solubilized product and unused water absorbent resin is dried.

[0029] In addition, a water absorbent resin obtained by using a used water absorbent resin or a solubilized product thereof as a part or all of a raw material is called a "recycled water absorbent resin composition". The recycled water absorbent resin composition may be a water absorbent resin before surface cross-linking or a water absorbent resin after surface cross-linking, regardless of whether or not the surface cross-linking is performed, but a water absorbent resin after surface cross-linking is preferable. The water absorbent resin before surface cross-linking may also be called a water absorbent resin precursor.

[0030] (Used water-absorbent resin) In the present invention, the term "used water absorbent resin" refers to a water absorbent resin contained in an absorbent article processed by a user of the water absorbent resin after shipment from a water absorbent resin factory; an absorbent article in which the absorbent article is sold and distributed and used by a consumer; or an absorbent article discarded after use. In addition, the used water absorbent resin may include a discarded water absorbent resin generated in the manufacturing process of the water absorbent resin, or a water absorbent resin contained in a water absorbent article discarded before use.

[0031] (Solubilized material of used water absorbent resin) In the present invention, the term "solubilized product of used water absorbent resin" means a polymer obtained by solubilizing the above-mentioned used water absorbent resin. More specifically, it means a polymer obtained by solubilizing the water absorbent resin by decomposing the main chain or crosslinking points of the water absorbent resin. The degree of solubilization and the molecular weight are appropriately determined, but the solubilization rate (mass%) of the water absorbent resin after the decomposition treatment is preferably high, and the water-soluble content (measured by pH titration after 16 hours extraction per 1.0 g of water absorbent resin) specified in EDANA470.02-02 (2002) is preferably 30 mass% or more, 50 mass% or more, 60 mass% or more, 70 mass% or more, 80 mass% or more, 90 mass% or more, and particularly 100 mass%. If the solubilization rate is low, the applications are limited both as a water absorbent resin and as a water-soluble resin, and this is not preferable. In particular, when the resin is used as a raw material for a water absorbent resin, the performance (for example, water absorption ratio) of the obtained water absorbent resin may be reduced. The mass average molecular weight Mw of the solubilized product is from 100 to 5,000,000, and the number average molecular weight is from 10,000 to 1,000,000, or from 100,000 to 800,000.

[0032] In the present invention, as a method for solubilizing a used water absorbent resin, the decomposition methods disclosed in the above Patent Documents 4 to 8 and other known documents are appropriately applied. Other known documents include, for example, JP-A-6-313008 (persulfate), JP-A-4-317784 (heat treatment at 40 ° C. in the presence of an oxidizing agent), JP-A-5-247307 (ascorbic acid), JP-A-2001-316519 (periodate), JP-A-9-249711 (acid or alkali), and JP-A-2020-116569 (water-soluble reducing agent and iron ions and / or copper ions). As long as a solubilized product of a used water absorbent resin can be obtained, there is no particular restriction.

[0033] (Method for producing a recycled water-absorbent resin composition using used water-absorbent resin or its solubilized material as a part or all of the raw material) In the present invention, the method for producing a recycled water absorbent resin composition using a used water absorbent resin or a solubilized product thereof as a part or all of a raw material is not particularly limited, and examples thereof include the following production methods (1) to (4). In other words, (1) A method for producing a recycled water-absorbent resin composition, as described in the above Patent Documents 1 to 3, which comprises separating and purifying a used water-absorbent resin from a used absorbent article (e.g., a used sanitary product) to obtain a hydrogel, and drying the resulting hydrogel; (2) As in the above Patent Documents 4, 7 to 11, a method for producing a recycled water absorbent resin composition, in which a used water absorbent resin is separated from a used absorbent article (e.g., a used sanitary product), and the solubilized water absorbent resin is applied to a production process of the water absorbent resin (e.g., a polymerization process); (3) As described in Patent Document 6, a method for producing a mixture of a recycled water absorbent resin composition and a virgin water absorbent resin by separating and purifying a used water absorbent resin from a used absorbent article (e.g., a used sanitary product), drying the purified water absorbent resin, and applying the resulting recycled water absorbent resin composition to a production process for a water absorbent resin (e.g., a surface cross-linking process); (4) A method for producing a recycled water-absorbent resin composition by separating used water-absorbent resin from used absorbent articles (e.g., used sanitary products) and re-crosslinking the solubilized water-absorbent resin (e.g., JP 2020-049398 A); Either of the above applies.

[0034] Here, the above (1) includes the drying of the above (A). The above (2) includes the drying of the above (B). In addition, the above (3) and (4) use the solubilized product of the used water absorbent resin after purification as part of the raw materials (however, in (4), most of the raw materials are other than the crosslinking agent) in the manufacturing process of the water absorbent resin, and the manufacturing process includes drying. In other words, all of the manufacturing methods (1) to (4) above have a drying process of the hydrogel of the used water absorbent resin or its solubilized product.

[0035] In the present invention, it is only necessary to include a step of drying a hydrogel of a used water absorbent resin or a solubilized product thereof, and other steps for producing a water absorbent resin, such as a polymerization step and a surface cross-linking step, may be known methods or methods that are currently novel, and are not particularly limited.

[0036] (Hydrate gel derived from used water-absorbent resin) The present invention assumes the recycling of water-absorbent resin from used absorbent articles (for example, used paper diapers with feces and urine attached thereto). Since such water-absorbent resin absorbs feces and urine and swells, when recycling, it is necessary to perform washing treatment, dehydration treatment, and sterilization treatment as necessary for the collected water-absorbent resin. Through the treatment, it becomes a hydrous gel derived from the used water-absorbent resin after purification. For the above-mentioned washing treatment, dehydration treatment, and sterilization treatment, the methods disclosed in the above-mentioned Patent Documents 1 to 3 and other known documents, for example, WO2021 / 162082, WO2022 / 091975, WO2023 / 007871, WO92 / 007995, JP-A-2013-150977, JP-A-2003-326161, etc. can be appropriately selected. In addition, there is no particular restriction as long as a hydrous gel of the used water-absorbent resin after purification can be obtained. The hydrogel of the used water absorbent resin of the present invention preferably has a solid content of 1% by mass or more and 95% by mass or less, and more preferably 10% by mass or more and 90% by mass or less.

[0037] In the present invention, when a used water absorbent resin or a solubilized product thereof is used as a part of a raw material, the used water absorbent resin or a solubilized product thereof is mixed with a water absorbent resin in the middle of production (particularly, an aqueous monomer solution before polymerization or a hydrous gel during or after polymerization) in a production process of a recycled water absorbent resin composition, preferably in a process before a drying process, particularly preferably in an arbitrary process between the polymerization process and the drying process.

[0038] The mixing ratio of the used water absorbent resin or a solubilized product thereof to the water absorbent resin in the middle of production is preferably 1 mass % or more and 60 mass % or less, more preferably 3 mass % or more and 50 mass % or less, particularly preferably 5 mass % or more and 40 mass % or less, based on the solid content of the monomer or hydrous gel of the water absorbent resin in the middle of production.

[0039] (Physical properties of hydrous gel) In the present invention, the hydrogel obtained by using a used water absorbent resin or a solubilized product thereof as a part or all of a raw material has a solid content of preferably 10 mass % or more and 90 mass % or less, more preferably 20 mass % or more and 80 mass % or less, further preferably 30 mass % or more and 70 mass % or less, particularly preferably 40 mass % or more and 60 mass % or less, in order to solve the problems of the present invention.

[0040] The residual monomer content of the hydrogel is preferably as small as possible, preferably 2% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less. If the residual monomer content is large, drying may become difficult, and coloring after drying or acrylamide, which is an impurity specific to recycling, may be produced as a by-product.

[0041] The CRC of the above-mentioned hydrogel is, in terms of dry mass, preferably 5 g / g or more and 80 g / g or less, more preferably 10 g / g or more and 50 g / g or less, even more preferably 15 g / g or more and 45 g / g or less, and particularly preferably 20 g / g or more and 40 g / g or less.

[0042] The water-soluble content (Ext) of the above-mentioned hydrogel is preferably 20% by mass or less, more preferably 15% by mass or less, further preferably 10% by mass or less, and particularly preferably 5% by mass or less, calculated on a dry mass basis.

[0043] (Temperature of hydrous gel) In the present invention, the hydrogel obtained by using the used water absorbent resin or its solubilized product as a part or all of the raw material is preferably heated to 40°C or higher, more preferably 50°C or higher, and even more preferably 60°C or higher in order to solve the problems of the present invention. On the other hand, in terms of effect and energy, it is preferably 110°C or lower, more preferably 100°C or lower, and even more preferably 90°C or lower. The temperature of the hydrogel can be appropriately adjusted in consideration of the polymerization temperature, aging after polymerization, heating or cooling, etc. Note that if the temperature of the hydrogel before drying is excessively high, it is not preferable because it may cause coloring of the obtained recycled water absorbent resin composition.

[0044] (Shape of hydrogel) In the present invention, the hydrogel obtained by using the used water absorbent resin or its solubilized product as a part or all of the raw material is preferably in the form of particles. The mass average particle diameter of the hydrogel is preferably 3 mm or less, more preferably 2 mm or less, 1 mm or less, 800 μm or less, 500 μm or less, and most preferably 400 μm or less. The larger the particle diameter of the hydrogel, the longer it takes to dry, which not only causes coloration and deterioration of physical properties, but also reduces the energy balance of drying, which is undesirable from the viewpoint of recycling.

[0045] In addition, the recycled water-absorbent resin composition is prone to a decrease in water absorption rate compared to unused water-absorbent resin due to impurities and damage during the regeneration process, but the water absorption rate can be restored or improved by setting the particle size of the hydrous gel before drying to the above range, particularly by crushing the gel to the above range.

[0046] The hydrogel before drying can also be obtained by classification or selection, and the particle size of the hydrogel can also be controlled by polymerization. From the viewpoint of ease of particle size control, however, it is preferable to include a gel crushing step before drying and to achieve a particle size in the above-mentioned range by the gel crushing.

[0047] (Residual urea amount) In the present invention, by subjecting a used water absorbent resin to a urea removal treatment such as washing, it is possible to reduce impurities derived from human waste contained in the water absorbent resin, thereby reducing coloration and the amount of residual monomers in the recycled water absorbent resin composition.

[0048] Among impurities derived from human waste, urea is known to have a high content and / or amount, and by setting the content of the urea to 4% by mass or less, 3% by mass or less, 2% by mass or less, 1.8% by mass or less, or 1.6% by mass or less, the deterioration of the water absorption performance of the recycled water absorbent resin composition can be prevented and coloring can be reduced. The lower the lower limit, the more preferable it is. However, in the present invention, even if some urea remains (for example, 0.01% by mass or even 0.1% by mass) without excessive purification, a recycled water absorbent resin composition with less coloring and less residual monomer can be obtained. In addition, excessive purification not only increases the cost of regeneration and deteriorates the recycled water absorbent resin composition, but is not preferable from the viewpoint of the consumed resources and energy, and the balance between the recycled resources and the consumed resources involved in regeneration. However, the present invention has an advantage in that such excessive purification is not required. The "amount of residual urea" means the urea content in the recycled water absorbent resin composition.

[0049] The method for quantifying the "amount of residual urea" is not particularly limited as long as it can quantify urea. For example, a method in which a water-absorbent resin is dispersed in water to extract the urea contained in the water-absorbent resin into an aqueous phase, and then the urea contained in the aqueous phase is directly quantified by liquid chromatography, gas chromatography, or the like. In addition, a method in which urea is quantified by a colorimetric method such as the urease indophenol method or the diacetyl monoxime method may be used.

[0050] Furthermore, by washing or dehydrating the used water absorbent resin, the amount of urea contained in the used water absorbent resin can be reduced to a target range.

[0051] (2) Surfactants or polymer dispersants In the present invention, in the (A) drying step of the hydrogel derived from the purified used water absorbent resin or (B) manufacturing step of the regenerated water absorbent resin composition including the polymerization step of the unsaturated monomer aqueous solution, in the drying step of the hydrogel obtained by using the purified used water absorbent resin or its solubilized product as a part of the raw material, the hydrogel is azeotropically dehydrated (first drying) in a hydrophobic organic solvent in the presence of a surfactant or a polymer dispersant. The surfactant or polymer dispersant may be present in the hydrogel, may be present in the hydrophobic solvent, or may be present in both the hydrogel and the hydrophobic organic solvent.

[0052] In the above-mentioned case of (A), in order to make a surfactant or a polymer dispersant present in a hydrogel derived from a used water absorbent resin after purification, the surfactant or the polymer dispersant may be used in the washing step, the sterilization step, or an optional dehydration step.

[0053] In the above case of (B), in the manufacturing process of the recycled water absorbent resin composition including the polymerization process of the unsaturated monomer aqueous solution, in order to make the surfactant or polymer dispersant present in the hydrogel obtained by using the used water absorbent resin or its solubilized product as a part of the raw material, the surfactant or polymer dispersant may be used in the used water absorbent resin or its solubilized product, or the surfactant or polymer dispersant may be present in the hydrogel of the unused water absorbent resin, or may be present in the hydrogel or hydrophobic organic solvent during azeotropic dehydration. In order to make the surfactant or polymer dispersant present in the hydrogel of the unused water absorbent resin, the surfactant or polymer dispersant may be used in the polymerization process of the unused water absorbent resin or any process after polymerization, for example, the gel crushing process.

[0054] The amount of the surfactant or polymer dispersant added is preferably 0.001% by mass or more and 5% by mass or less, more preferably 0.01% by mass or more and 3% by mass or less, and even more preferably 0.02% by mass or more and 2% by mass or less, based on the solid content of the hydrogel.

[0055] (Surfactant) The surfactants used in the present invention include anionic, cationic, nonionic and amphoteric surfactants, as well as low molecular weight or high molecular weight surfactants thereof, etc. Specifically, the surfactants are as follows, and two or more of them may be used in combination.

[0056] (a) a nonionic surfactant; Sucrose fatty acid esters, polyglycerol fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene glycerol fatty acid esters, sorbitol fatty acid esters, polyoxyethylene sorbitol fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, alkylaryl formaldehyde condensed polyoxyethylene ethers, polyoxyethylene polyoxypropylene block copolymers, polyoxyethylene polyoxypropyl alkyl ethers, polyethylene glycol fatty acid esters, alkyl glucosides, N-alkyl gluconamides, polyoxyethylene fatty acid amides, polyoxyethylene alkylamines, phosphate esters of polyoxyethylene alkyl ethers, and phosphate esters of polyoxyethylene alkyl allyl ethers.

[0057] (b) amphoteric surfactants; Alkyl dimethylaminoacetic acid betaines such as capryl dimethylaminoacetic acid betaine, lauryl dimethylaminoacetic acid betaine, myristyl dimethylaminoacetic acid betaine, and stearyl dimethylaminoacetic acid betaine; alkyl amidopropyl betaines such as lauric acid amidopropyl betaine, coconut oil fatty acid amidopropyl betaine, and palm kernel oil fatty acid amidopropyl betaine; alkyl hydroxysulfobetaines such as lauryl hydroxysulfobetaine; and alkyl carboxymethyl hydroxyethyl imidazolinium betaine such as 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine.

[0058] (c) anionic surfactants; Monoalkali metal alkylaminodiacetates such as monosodium laurylaminodiacetate, potassium laurylaminodiacetate, and sodium myristylaminodiacetate.

[0059] (d) cationic surfactants; Long-chain alkyl dimethylaminoethyl quaternary salts, etc.

[0060] Among these surfactants, from the viewpoint of dispersion stability, at least one selected from the group consisting of polyglycerol fatty acid ester, sucrose fatty acid ester, and sorbitan fatty acid ester is preferred. Examples of sucrose fatty acid ester include sucrose stearate, sucrose palmitate, sucrose oleate, sucrose laurate, sucrose myristic acid ester, sucrose behenate, and sucrose erucate. Note that sucrose fatty acid esters that are generally available on the market are mixtures of diesters and triesters with monoesters as the main component. Among these, sucrose stearate esters with monoesters as the main component and HLB of 1 to 16 depending on the composition of diesters and triesters are preferred.

[0061] (Polymer dispersant) The polymer dispersant used in the present invention may be a hydrophilic or hydrophobic polymer dispersant. Specifically, the following are listed, and two or more of them may be used in combination.

[0062] (e) hydrophobic polymeric dispersants; Maleic anhydride modified polyethylene, maleic anhydride modified polypropylene, maleic anhydride modified ethylene-propylene copolymer, maleic anhydride modified ethylene-propylene-diene terpolymer (EPDM), maleic anhydride modified polybutadiene, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, maleic anhydride-butadiene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, ethylene-acrylic acid copolymer, etc.

[0063] (f) hydrophilic polymeric dispersants; Ethyl cellulose, ethyl hydroxyethyl cellulose, polyalkylene oxides such as polyethylene glycol, polyvinyl alcohol, polyvinylpyrrolidone, etc.

[0064] The molecular weight (mass average molecular weight) of the polymer dispersant is preferably 200 or more and 2,000,000 or less, and more preferably 400 or more and 1,000,000 or less.

[0065] When a surfactant and a polymer dispersant are used in combination, the total amount of the surfactant and polymer dispersant is appropriately set according to the polymerization form, the composition of the monomer aqueous solution, and the water content of the hydrogel. When the surfactant and polymer dispersant are added to the monomer aqueous solution, the total amount is set to the concentration relative to the monomer component. When the surfactant and polymer dispersant are added to the hydrogel, the total amount is set to the concentration relative to the solid content of the hydrogel. Specifically, the total amount of the surfactant and polymer dispersant is preferably 1.0% by mass or less, more preferably 0.5% by mass or less, and more preferably 0.05% by mass or more, more preferably 0.1% by mass or more, relative to the solid content of the hydrogel to be dried.

[0066] (surface tension) In the present invention, the gel fluidizer may be selected in consideration of the fluidity of the hydrogel to be dried. In addition, the type and amount of the gel fluidizer that do not excessively reduce the surface tension of the final product are preferred, taking into consideration the amount of resorption during actual use of the absorbent article (paper diaper) using the obtained recycled water absorbent resin composition. For example, the type and amount of the gel fluidizer are selected so that the surface tension of the final product (surface tension of the dispersion of the water absorbent resin in physiological saline) is preferably 55 mN / m or more, more preferably 60 mN / m or more, and even more preferably 65 mN / m or more.

[0067] (3) A method for producing a hydrogel, which is applied to a process for producing a recycled water-absorbent resin composition, including a polymerization process of an aqueous solution of an unsaturated monomer (B) The polymerization method for the hydrogel obtained by using the above-mentioned (B) used water-absorbent resin or its solubilized product as a part of the raw material will be described below.

[0068] (monomer) In the present invention, the monomer may be any monomer used in water absorbent resins, but typically an aqueous solution containing acrylic acid as a main component (hereinafter referred to as "monomer aqueous solution") is used. Note that a monomer slurry may also be used within a range in which the water absorption performance of the resulting recycled water absorbent resin composition is not reduced. For convenience, the monomer aqueous solution will be described in this section.

[0069] The amount (content) of the acrylic acid (salt) used is usually 50 mol % or more, preferably 70 mol % or more, and more preferably 90 mol % or more (upper limit: 100 mol %), based on the total monomers (excluding the internal crosslinking agent) used in the polymerization reaction of the water absorbent resin.

[0070] The monomer other than acrylic acid may be any compound that can be polymerized to become a water-absorbent resin. Examples of the unsaturated monomers include methacrylic acid, (anhydrous) maleic acid, itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, 2-(meth)acryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, and 2-hydroxyethyl (meth)acryloyl phosphate; amide group-containing unsaturated monomers such as (meth)acrylamide, N-ethyl (meth)acrylamide, and N,N-dimethyl (meth)acrylamide; amino group-containing unsaturated monomers such as N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylamide; mercapto group-containing unsaturated monomers; phenolic hydroxyl group-containing unsaturated monomers; and lactam group-containing unsaturated monomers such as N-vinylpyrrolidone.

[0071] Among these, the monomer other than acrylic acid is, from the viewpoint of the water absorption performance of the obtained water absorbent resin, an acid group-containing unsaturated monomer, more preferably methacrylic acid, maleic acid (anhydride), itaconic acid, cinnamic acid, and even more preferably methacrylic acid.

[0072] In the case where an acid group-containing unsaturated monomer having an acid group such as a carboxyl group is used among acrylic acid and the above-mentioned monomers, it is more preferably an alkali metal salt, even more preferably at least one selected from the group consisting of sodium salts, lithium salts and potassium salts, and particularly preferably a sodium salt.

[0073] From the viewpoint of water absorption performance, the number of moles of the neutralization salt relative to the total number of moles of the acid group-containing unsaturated monomer and its neutralization salt (hereinafter referred to as "neutralization rate") is preferably 40 mol% or more, more preferably 40 mol% to 80 mol%, even more preferably 45 mol% to 78 mol%, and particularly preferably 50 mol% to 75 mol%. The adjustment of the neutralization rate may be performed before the start of the polymerization reaction of the acid group-containing unsaturated monomer, during the polymerization reaction of the acid group-containing unsaturated monomer, or on the hydrogel-like crosslinked polymer obtained after the polymerization reaction of the acid group-containing unsaturated monomer is completed. In addition, the neutralization rate may be adjusted by selecting one of the stages before the start of the polymerization reaction, during the polymerization reaction, or after the polymerization reaction is completed, or the neutralization rate may be adjusted at multiple stages.

[0074] (Internal crosslinking agent) In the present invention, an internal crosslinking agent is preferably used, which adjusts the water absorption performance and gel strength of the resulting recycled water-absorbent resin composition when it absorbs water.

[0075] The internal crosslinking agent may have a total of two or more unsaturated bonds or reactive functional groups in one molecule. For example, N,N-methylenebis(meth)acrylamide, (poly)ethylene glycol di(meth)acrylate, ethylene glycol diglycidyl ether, glycidyl (meth)acrylate, etc. may be mentioned. Among these, two or more may be used in combination. The amount of the internal crosslinking agent used is preferably 0.001 mol% or more and 5 mol% or less, more preferably 0.005 mol% or more and 2 mol% or less, based on the monomer.

[0076] (Amount of used water absorbent resin or its solubilized material added) In the above method (B), the used water absorbent resin or the solubilized product thereof is added to and mixed with the monomer or the hydrogel in the middle of production. The amount of the used water absorbent resin or the solubilized product thereof is preferably 1% by mass or more and 60% by mass or less, more preferably 3% by mass or more and 50% by mass or less, and further preferably 5% by mass or more and 40% by mass or less, based on the solid content of the monomer or the hydrogel in the middle of production.

[0077] (monomer concentration) In the present invention, the monomer concentration in the aqueous monomer solution (=total monomer amount / (total monomer amount+total polymerization solvent amount (usually water)) is preferably 10 mass% or more and 90 mass% or less, more preferably 20 mass% or more and 80 mass% or less, further preferably 30 mass% or more and 70 mass% or less, and particularly preferably 40 mass% or more and 60 mass% or less, from the viewpoint of the physical properties and productivity of the recycled water absorbent resin composition.

[0078] (Other additives) In the production method according to the present invention, the following substances (hereinafter referred to as "other substances") may be added to the aqueous monomer solution within the scope of achieving the object of the present invention.

[0079] Specific examples of other substances include chain transfer agents such as thiols, thiolic acids, secondary alcohols, amines, and hypophosphites; foaming agents such as carbonates, bicarbonates, azo compounds, and bubbles; chelating agents such as ethylenediaminetetra(methylenephosphinic acid) and metal salts thereof, ethylenediaminetetraacetic acid and metal salts thereof, and diethylenetriaminepentaacetic acid and metal salts thereof; hydrophilic polymers such as polyacrylic acid (salts) and crosslinked products thereof (for example, recycled water-absorbent resin fine powder), starch, cellulose, starch-cellulose derivatives, and polyvinyl alcohol. The other substances may be used alone or in combination of two or more.

[0080] The amount of other substances used is not particularly limited, but in the case of recycled fine powder, it is 30% by mass or less relative to the monomer, and in the case of other than fine powder, the total concentration of other substances is preferably 10% by mass or less relative to the monomer, more preferably 0.001% by mass or more and 5% by mass or less, and particularly preferably 0.01% by mass or more and 1% by mass or less.

[0081] (Polymerization initiator) The polymerization initiator used in the present invention is not particularly limited since it is appropriately selected depending on the polymerization form, etc., but examples thereof include a thermal decomposition type polymerization initiator, a photodecomposition type polymerization initiator, or a combination of these, or a redox type polymerization initiator combined with a reducing agent that promotes the decomposition of the polymerization initiator. In particular, a peroxide or an azo compound, more preferably a peroxide, and even more preferably a persulfate, are used. The amount of the polymerization initiator used is preferably 0.001 mol% or more and 1 mol% or less, more preferably 0.001 mol% or more and 0.5 mol% or less, based on the monomer. The amount of the reducing agent used is preferably 0.0001 mol% or more and 0.02 mol% or less, based on the monomer.

[0082] (Polymerization method) It is also preferable to reduce the dissolved oxygen in the aqueous monomer solution before polymerization by raising the temperature or replacing it with an inert gas. For example, the dissolved oxygen is preferably reduced to 5 ppm or less, more preferably 3 ppm or less, and particularly preferably 1 ppm or less. Also, air bubbles (particularly the above-mentioned inert gases, etc.) can be dispersed in the aqueous monomer solution. In this case, the polymerization reaction becomes foaming polymerization.

[0083] The polymerization form is not particularly limited. From the viewpoint of water absorption characteristics, ease of polymerization control, etc., preferably, droplet polymerization in a gas phase, aqueous solution polymerization, and reversed-phase suspension polymerization (here, droplet polymerization in a hydrophobic organic solvent is also included as an example of reversed-phase suspension), and more preferably, aqueous solution polymerization and reversed-phase suspension polymerization are used.

[0084] In the present invention, by using a hydrogel using the surfactant or polymer dispersant of (2) in these polymerization steps, a hydrogel of a water-absorbent resin obtained by using, as a part of a raw material, a used water-absorbent resin after purification or a solubilized product thereof in a production step of a water-absorbent resin including a polymerization step of (B) an unsaturated monomer aqueous solution, may be subjected to azeotropic dehydration in a hydrophobic solvent in the presence of a surfactant or polymer dispersant until a hydropolymer having a water content of 5 mass % or more and 50 mass % or less is obtained.

[0085] (Gel crushing process) This step is a step of pulverizing the hydrogel crosslinked polymer obtained in the polymerization step simultaneously with and / or after polymerization to obtain fine particles, for example, a step of pulverizing the hydrogel crosslinked polymer by a device such as a screw extruder such as a kneader or a meat chopper, a cutter mill, etc. to obtain a particulate hydrogel crosslinked polymer (hereinafter, "particulate hydrogel"). The preferred particle size is in the range described later, and the step is carried out so that the shape and size of the granular dried product obtained in the heat drying step described later or the post-crosslinked granular dried product obtained in the post-crosslinking step approach the desired product particle size.

[0086] In the present invention, a hydrogel using the above-mentioned surfactant or polymer dispersant is used in these gel crushing steps to obtain a hydrogel of a water-absorbent resin obtained by using, as a part of a raw material, a used water-absorbent resin after purification or a solubilized product thereof in a production step of a water-absorbent resin including a polymerization step of (B) an unsaturated monomer aqueous solution, so that the hydrogel can be azeotropically dehydrated in a hydrophobic solvent in the presence of a surfactant or polymer dispersant until the hydropolymer has a water content of 5 mass % or more and 50 mass % or less.

[0087] In the gel pulverization, in (B), a used water absorbent resin or a solubilized material thereof is mixed with a monomer of a water absorbent resin or a solid content of a hydrous gel in the middle of production in an amount of 1 mass % or more and 60 mass % or less, further 3 mass % or more and 50 mass % or less, particularly 5 mass % or more and 40 mass % or less.

[0088] (4) Drying method of hydrogel The drying method of the present invention is a method for producing a recycled water-absorbent resin composition using a used water-absorbent resin, which comprises carrying out azeotropic dehydration (first drying) in a hydrophobic organic solvent in the presence of a surfactant or a polymer dispersant to obtain a hydrogel-like crosslinked polymer having a water content of 5% by mass or more and 50% by mass or less, filtering or evaporating to dryness to separate the hydrophobic organic solvent from the hydrogel crosslinked polymer, and further carrying out heating and drying (second drying) under stirring to obtain a dried polymer having a water content of 1% by mass or more and 20% by mass or less. This is a method for producing a recycled water-absorbent resin composition.

[0089] (4-1) Azeotropic dehydration of hydrous gel (first drying) (Hydrophobic Solvent) Specific examples of organic solvents used for azeotropy include aliphatic hydrocarbons such as pentane, hexane, and heptane, alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclohexane, aromatic hydrocarbons such as benzene, toluene, and xylene, chlorinated hydrocarbons such as methylene chloride, chloroform, carbon tetrachloride, trichlene, perchlorene, ethylene dichloride, and benzene chloride, methyl acetate, ethyl acetate, propyl acetate, and acetonitrile. Hexane, heptane, cyclohexane, benzene, and toluene are particularly preferred.

[0090] As hydrophobic solvents, it is preferred to use aliphatic hydrocarbons, such as n-hexane, n-heptane, n-octane, n-nonane, n-decane, cyclohexane or mixtures thereof. The hydrophobic solvent has a solubility in water at 23° C. of less than 5 g / 100 g, advantageously less than 1 g / 100 g, particularly preferably less than 0.5 g / 100 g.

[0091] (solid-liquid ratio) The ratio of the hydrophobic solvent to the hydrous gel is 0.5 to 3, preferably 0.7 to 2.5, and most preferably 0.8 to 2.2.

[0092] (Particle size of hydrogel) The above-mentioned particle size of the hydrogel is preferably applied, and the hydrogel is dried as a particulate hydrogel.

[0093] (Surfactant or polymer dispersant) The above-mentioned surfactant or polymer dispersant may be present in the hydrogel, may be present in the hydrophobic solvent, or may be present in both the hydrogel and the hydrophobic solvent.

[0094] (Drying equipment and mixing) The azeotropic dehydration of the hydrous gel is carried out in a drying vessel filled with a hydrophobic organic solvent, and preferably the hydrous gel is stirred in the hydrophobic organic solvent. An example of a drying vessel suitable for azeotropic dehydration is one having stirring blades (particularly paddle blades, and further lattice-shaped stirring blades (lattice blades). Furthermore, it is also preferable to provide a plurality of baffle plates along the direction of the rotation axis on the side wall surface of the drying vessel.

[0095] (pressure) The drying pressure may be normal, elevated or reduced pressure as appropriate, and in azeotropic dehydration, the boiling point of the reaction mixture can be adjusted to a desired reaction temperature by adjusting the pressure.

[0096] (moisture content) In carrying out the present invention, the hydrogel is subjected to azeotropic dehydration as the first drying step until the water content of the hydrogel is preferably 10% by mass or more and 50% by mass or less, more preferably 12% by mass or more and 35% by mass or less, and even more preferably 15% by mass or more and 40% by mass or less.

[0097] When the above-mentioned azeotropic dehydration is carried out only until the water content of the hydrous gel exceeds 50 mass %, not only does it take a long time in the second drying described later and is likely to cause coloring, but also there is a risk that the amount of residual monomers increases after drying in the hydrous gel obtained by using the used water absorbent resin or a solubilized product thereof (B) as a part of the raw material.

[0098] Furthermore, the above-mentioned azeotropic dehydration is not preferable because a large amount of a hydrophobic organic solvent is required to dry the hydrogel until the water content becomes less than 10% by mass, and the drying efficiency drops sharply at a water content of less than 10% by mass, requiring a long period of time for drying, resulting in poor energy balance and the risk of coloration.

[0099] (Operation after azeotropic dehydration) After the azeotropic dehydration, the hydrogel having a water content of 10% by mass or more and 50% by mass or less is separated from the hydrophobic organic solvent by either evaporating the hydrophobic organic solvent to dryness or by filtration. The hydrogel after the azeotropic dehydration or the hydrogel separated from the hydrophobic organic solvent is sometimes called a "semi-dried gel" to distinguish it from the hydrogel to be subjected to azeotropic dehydration.

[0100] (4-2) Heat drying (second drying) The semi-dried gel (water-containing gel) having a water content of 10% by mass or more and 50% by mass or less, which has been separated from the hydrophobic organic solvent by the above-mentioned evaporation to dryness or filtration, is dried by a known means such as a groove-type dryer, a shelf-type vacuum dryer, a vacuum dryer equipped with a stirrer, a rotary dryer, a fluidized bed dryer, an airflow dryer, or a plate dryer.

[0101] (Mixing, heating and drying equipment) In the production method according to the present invention, a particulate semi-dried gel having a moisture content of 10% by mass or more and 50% by mass or less after azeotropic dehydration (first drying) is stirred and heated and dried. The stirring and heating drying may be batch drying, continuous drying, or semi-continuous drying. Drying methods that do not fall under the category of stirring and heating drying include static drying (especially static hot air drying), freeze drying, dehydration drying with a hydrophilic solvent, and contact drying with a drum dryer, but these drying methods and drying forms are insufficient for solving the problems of the present invention.

[0102] Examples of the stirring method include a container rotary dryer in which the container in which the material is placed rotates, or an agitation dryer having an agitation blade for the material, and further a fluidized bed dryer in which the material is fluidized by air current, and these stirring functions may be used in combination. There is no particular limitation as long as the device has the function of fluidizing and drying the particulate semi-dried gel, and as a means for fluidizing the particulate semi-dried gel, the material may be placed inside a rotating container as shown in Figure 1 or Figure 2 and then agitated and dried, or the material may be fluidized by hot air as in a fluidized bed as shown in Figure 3, or a paddle dryer as shown in Figure 4 may be used.

[0103] Also usable is a dryer (rotary dryer) in which agitation is performed by rotating a cylindrical or other container that contains the material to be dried. Specific examples of the rotary dryer include a rotary dryer (Okawahara Works Co., Ltd.), a rotary kiln (Kurimoto Works Co., Ltd.), and a steam tube dryer (Kurimoto Works Co., Ltd., Ube Machinery Co., Ltd., Tsukishima Kikai Co., Ltd., and Mitsui Zosen Co., Ltd.). Other drying devices that can be used include a single-shaft or twin-shaft disk dryer, a single-shaft or twin-shaft paddle dryer, a CD dryer (manufactured by Kurimoto Works Co., Ltd.), and a paddle dryer (manufactured by Nara Machinery Co., Ltd.).

[0104] In the case of an agitation dryer, the rotation speed of the rotating shaft is appropriately set depending on the device. The specific rotation speed is usually in the range of 1 rpm to 10,000 rpm, preferably 5 rpm to 500 rpm, and more preferably 10 rpm to 300 rpm.

[0105] In addition, the circumferential speed of the rotating shaft (circumferential speed (V) (m / s) = 2πr × n / 60) is not particularly limited, but is preferably 0.05 m / s or more and 10 m / s or less, more preferably 0.1 m / s or more and 8 m / s or less, and even more preferably 0.15 m / s or more and 5 m / s or less.

[0106] In the present invention, it is preferable to introduce an air current into the above-mentioned agitation type drying device. In the agitation drying, the material to be dried (semi-dried gel) is fluidized, and foreign matter (particularly fine particles and pulp with a light specific gravity) can be removed by the air current while drying. The carrier gas may be at room temperature as long as the inner wall of the drying vessel is heated, but is preferably heated to 100°C or higher.

[0107] (Drying temperature, drying time) In the present invention, the drying temperature (heat medium temperature or material temperature) in the second drying is preferably 50°C or more and 160°C or less, more preferably 60°C or more and 150°C or less. When the drying temperature is within this range, coloration of the dried polymer after drying can be suppressed even if a used water absorbent resin or its solubilized material is used as a part or all of the raw material. In addition, the drying time in the second drying is preferably 10 minutes or more and 120 minutes or less, more preferably 20 minutes or more and 90 minutes or less, and even more preferably 20 minutes to 60 minutes.

[0108] (Moisture content of dried polymer) In the present invention, the moisture content of the dried polymer obtained through the first drying and the second drying is in the range of 1% by mass to 20% by mass, preferably 2% by mass to 15% by mass, more preferably 3% by mass to 10% by mass. By setting the moisture content within this range, even if a used water absorbent resin or a solubilized product thereof is used as a part or all of the raw material, coloration of the dried polymer after drying can be suppressed.

[0109] (Airflow and Pressure) The above-mentioned stirring dryer can also have a function of pressurizing, normal pressure or reduced pressure inside the device. When the pressure is increased, the pressure is adjusted, for example, by increasing the amount of carrier gas introduced into the dryer. Preferably, the degree of pressurization relative to atmospheric pressure is a slight pressure of more than 0 and not more than 0.01 kPa. When the pressure is reduced, the pressure is adjusted, for example, by changing the amount of exhaust gas (water vapor generated by drying and carrier gas to be introduced) from the dryer. The degree of reduced pressure relative to atmospheric pressure is preferably a slight pressure of more than 0 kPa and not more than 5 kPa, more preferably more than 0 kPa and not more than 2 kPa, and even more preferably 0.01 kPa or more and not more than 0.5 kPa. By applying a slight reduced pressure or slight pressurization, it becomes easier to remove foreign matter by the carrier gas (air flow), which is preferable. The amount of the carrier gas (air flow) introduced is preferably 0.05 Nm3 relative to the processing amount per unit time (kg / hr) calculated as the solid content of the hydrous gel (semi-dried gel) introduced in the second drying. 3 / kg or more 20Nm 3 / kg or less, more preferably 0.1Nm 3 / kg or more 10Nm3 / kg or less, more preferably 0.1 Nm 3 / kg or more 5Nm 3 / kg or less, particularly preferably 0.2 Nm 3 / kg or more 2.5Nm 3 / kg or less, most preferably 0.2Nm 3 / kg or more 1Nm 3 / kg or less.

[0110] (Particle size of dried polymer after drying) In the present invention, the particle size (particle size) of the dried polymer after drying (defined by sieve classification) is preferably 3 mm or less, more preferably 2 mm or less, and even more preferably 1 mm or less, for 60% or more by mass of the total amount of the dried polymer. With this configuration, foreign matter (e.g., pulp derived from sanitary products, etc.) can be removed more efficiently. If the particle size is too large, foreign matter may be taken into the inside of the dried polymer, making it difficult to remove the foreign matter during or after drying (e.g., removal of pulp derived from sanitary products by air flow or classification with a sieve, etc.).

[0111] (Cooling after drying) In order to solve the problems of the present invention, it is preferable to cool the dried polymer after the drying. The temperature of the dried polymer after cooling is preferably 100°C or less, more preferably 90°C or less, and even more preferably 85°C or less (the lower limit is 40°C or 50°C). If cooling is not performed, the dried polymer may be discolored or aggregated, and further, it may be difficult to control the particle size during pulverization. If pulverization is difficult, it may also be difficult to remove foreign matter during classification after pulverization (for example, removal during classification of pulp derived from sanitary products).

[0112] The cooling method is not particularly limited, but it is preferable to use a continuous cooler having a cooling means of ventilation heat transfer type or conductive heat transfer type, or a stirrer having a rotating shaft. A mixer having a function of ventilating an air current through the object to be cooled and cooling it is widely used as a cooler.

[0113] (4-3) Other additives added during drying In the drying of the hydrogel in the present invention, a surfactant or a polymer dispersant is used, but in order to achieve the object of the present invention, it is preferable to use a chelating agent and / or a reducing agent.

[0114] (chelating agent) In the drying step of the present invention, it is preferable that a chelating agent is further present. With this configuration, coloring and performance deterioration resulting from the used water absorbent resin or its solubilized product are further suppressed. The chelating agent is preferably contained in the hydrogel before drying, and the chelating agent may be added to the used water absorbent resin or its solubilized product, or the chelating agent may be added to the monomer in the polymerization step of the recycled water absorbent resin composition obtained by using the used water absorbent resin or its solubilized product as a part or all of the raw material, or to the hydrogel after polymerization. When the chelating agent is added after polymerization, it is also preferable to mix the chelating agent with the hydrogel before drying and mix the chelating agent uniformly by gel crushing.

[0115] The chelating agent to be used is preferably a polymeric compound or a non-polymeric compound, more preferably a non-polymeric compound, and is preferably a chelating agent containing an element other than carbon, hydrogen, and oxygen, more preferably nitrogen or phosphorus, in the molecule.

[0116] Specific examples of the chelating agent used in the present invention include hydroxy polycarboxylic acids, amino polycarboxylic acids, organic polyphosphates, inorganic polyphosphates, amino polyphosphates, and tropolone derivatives. At least one compound selected from the group consisting of these compounds is applied in the present invention. The above-mentioned "polyvalent" refers to having multiple functional groups in one molecule, preferably 2 to 30 functional groups, more preferably 3 to 20 functional groups, and even more preferably 4 to 10 functional groups.

[0117] From the viewpoint of the effect on polymerization and the physical properties of the resulting recycled water absorbent resin composition, the molecular weight of the chelating agent is preferably from 100 to 5000, more preferably from 200 to 1000. If the molecular weight exceeds 5000, the aqueous monomer solution may thicken depending on the timing of addition of the chelating agent, which is undesirable because it makes it difficult to control polymerization and mix uniformly.

[0118] Specific examples of the amino polycarboxylic acid include iminodiacetic acid, hydroxyethyliminodiacetic acid, nitrilotriacetic acid, nitrilotripropionic acid, ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, trans-1,2-diaminocyclohexanetetraacetic acid, N,N-bis(2-hydroxyethyl)glycine, diaminopropanoltetraacetic acid, ethylenediamine2propionic acid, N-hydroxyethylethylenediaminetriacetic acid, glycol ether diaminetetraacetic acid, diaminopropanetetraacetic acid, N,N'-bis(2-hydroxybenzyl)ethylenediamine-N,N'-diacetic acid, 1,6-hexamethylenediamine-N,N,N',N'-tetraacetic acid, and salts thereof.

[0119] Specific examples of the organic polyphosphate include nitriloacetic acid-di(methylenephosphinic acid), nitrilodiacetic acid-(methylenephosphinic acid), nitriloacetic acid-β-propionic acid-methylenephosphonic acid, nitrilotris(methylenephosphonic acid), and 1-hydroxyethylidene diphosphonic acid.

[0120] Specific examples of the inorganic polyphosphate include pyrophosphoric acid, tripolyphosphoric acid, and salts thereof.

[0121] Specific examples of the hydroxy polyvalent carboxylic acid include malic acid, citric acid, and salts thereof.

[0122] Specific examples of the amino polyphosphate include ethylenediamine-N,N'-di(methylenephosphinic acid), ethylenediaminetetra(methylenephosphinic acid), cyclohexanediaminetetra(methylenephosphonic acid), ethylenediamine-N,N'-diacetic acid-N,N'-di(methylenephosphonic acid), ethylenediamine-N,N'-di(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), polymethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), and salts thereof.

[0123] Specific examples of the tropolone derivative include tropolone, β-thujaplicin, and γ-thujaplicin.

[0124] Among these, chelating agents selected from amino polycarboxylic acids, organic polyphosphates, and amino polyphosphates are preferred, amino polycarboxylic acid-based chelating agents having three or more carboxyl groups are more preferred, and from the viewpoint of gel stability, diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, trans-1,2-diaminocyclohexanetetraacetic acid, and salts thereof are even more preferred.

[0125] In the present invention, the content (amount used) of the chelating agent is 0.001 parts by mass or more and 5 parts by mass or less, preferably 0.02 parts by mass or more and 1 part by mass or less, more preferably 0.03 parts by mass or more and 0.9 parts by mass or less, even more preferably 0.04 parts by mass or more and 0.8 parts by mass or less, still more preferably 0.05 parts by mass or more and 0.7 parts by mass or less, particularly preferably 0.06 parts by mass or more and 0.6 parts by mass or less, and most preferably 0.07 parts by mass or more and 0.5 parts by mass or less, relative to 100 parts by mass of the solid content of the water absorbent resin.

[0126] (reducing agent) In the present invention, it is preferable to further add a reducing agent, particularly a sulfur-based inorganic or organic reducing agent, during and / or after drying. With such a configuration, coloration and performance deterioration of the recycled water absorbent resin composition are further suppressed. In addition, the by-production of acrylamide in the recycled water absorbent resin composition can also be suppressed. The reducing agent is preferably contained in the hydrogel before drying, and may be added to the used water absorbent resin or its solubilized product, or may be added to the hydrogel after polymerization obtained in the polymerization step of the recycled water absorbent resin composition obtained by using the used water absorbent resin or its solubilized product as a part or all of the raw material. When adding a reducing agent after polymerization, it is also preferable to mix the reducing agent with the hydrogel before drying and mix the reducing agent uniformly by gel crushing.

[0127] The reducing agent is preferably a sulfur-based inorganic or organic reducing agent, and examples of such reducing agents include inorganic reducing agents such as sodium sulfite, potassium sulfite, calcium sulfite, ammonium sulfite, sulfurous acid, sodium hydrogen sulfite, potassium hydrogen sulfite, ammonium hydrogen sulfite, sodium thiosulfate, potassium thiosulfate, ammonium thiosulfate, and magnesium thiosulfate, and organic reducing agents such as 2-hydroxy-2-sulfinatoacetic acid, 2-hydroxy-2-sulfonatoacetic acid, cysteine, and cystine, and one or more of these can be used. Among these, sulfites and hydrogen sulfites are preferred in terms of effectiveness and cost.

[0128] In addition, the amount of the sulfur-containing reducing agent is preferably 0.05 parts by mass or more and 10 parts by mass or less, more preferably 0.1 parts by mass or more and 8 parts by mass or less, relative to 100 parts by mass of the solid content of the water absorbent resin. When the amount of the sulfur-containing reducing agent used is less than 0.05 parts by mass, the desired effect of reducing the residual monomer may not be obtained. When the amount of the sulfur-containing reducing agent used is more than 10 parts by mass, the amount of the agent is excessive for the required effect of reducing the residual monomer, which may lead to a decrease in physical properties, and is uneconomical in terms of cost. When the additive containing the sulfur-containing reducing agent is added in the form of an aqueous solution, the amount is preferably 0.001% by mass or more and 50% by mass or less relative to the aqueous solution. In the present invention, the additive is selectively and preferentially added to the surface of the particles and the fine particles, so a small amount is sufficient and the physical properties are not decreased.

[0129] (5) Post-drying process (Crushing process, classification process) The dried polymer obtained after the drying may be subjected to a pulverization step or a classification step. By such a configuration, foreign matter can be removed, and in particular, by including a surfactant in the dried polymer, the amount of foreign matter such as pulp can be further reduced, and the water absorption performance can be further restored or improved.

[0130] In the present invention, from the viewpoint of water absorption performance and removal of foreign matter in classification, the mass average particle diameter of the water absorbent resin obtained through the classification step is preferably 200 μm to 600 μm, more preferably 250 μm to 550 μm, and even more preferably 300 μm to 500 μm. From the viewpoint of the quality of the obtained recycled water absorbent resin composition, it is preferable that the recycled water absorbent resin composition is mainly composed of particles having a particle diameter of 150 μm to 850 μm as defined by sieve classification. The ratio of particles having a particle diameter of 150 μm to 850 μm in the recycled water absorbent resin composition is preferably 90% by mass to 100% by mass, more preferably 95% by mass to 100% by mass, even more preferably 97% by mass to 100% by mass, and particularly preferably 99% by mass to 100% by mass. Therefore, the proportion of particles having a particle size of less than 150 μm or more than 850 μm as determined by sieve classification is preferably 10 mass % or less, more preferably 5 mass % or less, further preferably 3 mass % or less, and particularly preferably 1 mass %.

[0131] (Surface crosslinking process) This step is a step of adding a surface crosslinking agent that reacts with the functional group (particularly carboxyl group) of the water-absorbent resin to the hydrogel after polymerization or its dried polymer to cause a crosslinking reaction. The crosslinking reaction is also called surface crosslinking or secondary crosslinking because crosslinking mainly occurs from the surface of the water-absorbent resin. In the production method according to the present invention, a surface crosslinking agent is added to the water-absorbent resin after the pulverization or classification during or after drying, particularly after drying, to cause a reaction. The surface crosslinking step includes a step of adding a surface crosslinking agent and a heat treatment step, and may include a cooling step after the heat treatment step as necessary.

[0132] In the present invention, as the surface crosslinking agent, a surface crosslinking agent capable of reacting with a plurality of functional groups (preferably a plurality of carboxyl groups) of the water-absorbing resin, preferably a surface crosslinking agent capable of covalent bonding or ionic bonding, further a surface crosslinking agent capable of covalent bonding, is used.Specific examples thereof include polyhydric alcohol compounds such as ethylene glycol, diethylene glycol, propylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, 1,3-propanediol, 2-butene-1,4-diol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol; epoxy compounds such as ethylene glycol diglycidyl ether and polyethylene glycol diglycidyl ether; alkylene carbonate compounds such as 1,3-dioxolane-2-one and 4-methyl-1,3-dioxolane-2-one; and the like.

[0133] The amount of the surface cross-linking agent added is preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 2% by mass or less, based on the solid content of the water absorbent resin during or after drying. The lower limit is preferably 0.001% by mass.

[0134] The surface cross-linking agent may be added as it is, but is preferably added in a solution state dissolved in water or an organic solvent for ease of addition. The concentration of the surface cross-linking agent solution is preferably 1% by mass or more, more preferably 2% by mass or more. The total amount of the solvent selected from water and an organic solvent is preferably 0% by mass or more and 10% by mass or less, more preferably 0.1% by mass or more and 8% by mass or less, and even more preferably 0.5% by mass or more and 5% by mass or less, based on the solid content of the water absorbent resin. When water and an organic solvent are used in combination, it is preferable that water is the main component.

[0135] The water-absorbent resin containing the surface cross-linking agent is heated to 100°C or higher to obtain a surface-cross-linked water-absorbent resin. The preferred maximum temperature varies depending on the type of surface cross-linking agent, but is preferably 100°C or higher and 250°C or lower, more preferably 120°C or higher and 230°C or lower, and even more preferably 150°C or higher and 210°C or lower. The time of the heat treatment step may be appropriately set based on the water content of the water-absorbent resin, the type of the surface cross-linking agent, the thermal efficiency of the heating device, and the like. As a rough guide, heating may be performed until the water content becomes 10% by mass or lower, and the time is in the range of 10 minutes to 120 minutes, preferably 30 minutes to 90 minutes. After the surface cross-linking, the reaction may be stopped by cooling as desired.

[0136] (Other processes) The manufacturing method according to the present invention may also include, as other steps, a step of adding additives such as inorganic fine particles, dust inhibitors, fungicides, antibacterial agents, antioxidants, ultraviolet absorbers, colorants, fragrances, deodorants, and organic fibrous materials before or after drying. When these additives are added, the content (mass%) of the additives is preferably 0.001% by mass or more and 10% by mass or less, more preferably 0.01% by mass or more and 5% by mass or less, still more preferably 0.05% by mass or more and 1% by mass or less, and particularly preferably 0.1% by mass or more and 0.5% by mass or less, based on the mass of the water absorbent resin. Specific examples of the inorganic fine particles include minerals such as hydrotalcite; silicon oxide, titanium oxide, and aluminum oxide.

[0137] (6) Properties of Recycled Water-Absorbent Resin Composition The recycled water-absorbent resin composition obtained above has less coloring and foreign matter, and can be used in a wider range than conventional recycled water-absorbent resin compositions. The recycled water-absorbent resin composition obtained has the following properties:

[0138] The YI value (Yellow-Index) of the recycled water absorbent resin composition of the present invention is preferably not more than 20, more preferably not more than 15. By virtue of this constitution, the substantially white recycled water absorbent resin composition can be used in a wider range of applications.

[0139] The residual monomer content of the recycled water absorbent resin composition of the present invention is preferably 300 ppm or less, more preferably 200 ppm or less, and further preferably 100 ppm or less. With such a constitution, the recycled water absorbent resin composition can be used in a wider range of applications, and the by-production of acrylamide can be suppressed.

[0140] The amount of the hydrophobic organic solvent contained in the recycled water absorbent resin composition of the present invention is preferably 1 mass % or less, more preferably 0.5 mass % or less, further preferably 0.1 mass % or less, and particularly preferably 0.05 mass % or less. The lower limit is preferably 1 ppm, more preferably about 10 ppm. The amount of the hydrophobic organic solvent contained in the recycled water absorbent resin composition is quantified by the following method.

[0141] (Quantitative determination of hydrophobic organic solvents) DMF and a 25% by mass phosphoric acid aqueous solution were prepared. 0.10 g of the regenerated water absorbent resin composition was precisely weighed into a vial with an internal volume of 20 mL. 4 mL of DMF and 5 mL of a 25% by mass phosphoric acid aqueous solution were added to this vial. The vial was quickly sealed using a septum rubber and an aluminum cap, and the vial was shaken and mixed for 1 minute. The above vial was heated at 110°C for 2 hours while being shaken and mixed, and then 1 mL of the gas phase was injected into a gas chromatograph to obtain a chromatogram. The amount of the hydrocarbon dispersion medium contained in the regenerated water absorbent resin composition (precisely weighed value of 0.10 g) was calculated from the peak area of ​​the obtained chromatogram and the calibration curve created earlier. The calculated value was converted to a value per 1 g of the regenerated water absorbent resin composition and used as the amount of remaining volatile components (mass%).

[0142] The amount of magnesium and calcium contained in the recycled water absorbent resin composition of the present invention is preferably 1 ppm or more and 1000 ppm or less. With this constitution, the recycled water absorbent resin composition can suppress the performance degradation and can be used in a wider range.

[0143] The amount of urea and ammonia contained in the recycled water absorbent resin composition of the present invention is preferably 4 mass % or less, more preferably 3 mass % or less, further preferably 2 mass % or less, and particularly preferably 1 mass % or less. With such a constitution, the performance deterioration of the recycled water absorbent resin composition can be suppressed, and it can be used in a wider range.

[0144] The amount of foreign matter (typified by pulp) contained in the recycled water absorbent resin composition of the present invention is preferably 1 mass % or less, more preferably 0.5 mass % or less, and further preferably 0.1 mass % or less.

[0145] The recycled water absorbent resin composition of the present invention has a high water absorption capacity (high CRC) even though it is made of a used water absorbent resin or its solubilized product as a part or all of the raw material. The CRC is preferably 15 g / g or more, more preferably 25 g / g or more. There is no particular restriction on the upper limit, and a higher CRC is preferable, but from the viewpoint of the balance with other physical properties, it is preferably 70 g / g or less, more preferably 50 g / g or less, and even more preferably 40 g / g or less.

[0146] The recycled water absorbent resin composition of the present invention has a high water absorption capacity under pressure (high AAP) even though used water absorbent resin or its solubilized product is used as a part or all of the raw material. The AAP is preferably 15 g / g or more, more preferably 20 g / g or more, even more preferably 22 g / g or more, particularly preferably 23 g / g or more, and most preferably 24 g / g or more. The upper limit is not particularly limited, but is preferably 30 g / g or less.

[0147] The recycled water absorbent resin composition of the present invention has a low water-soluble content, even though it is made of a used water absorbent resin or a solubilized product thereof as a part or all of the raw material. The water-soluble content is usually 50 mass % or less, preferably 35 mass % or less, more preferably 25 mass % or less, and further preferably 15 mass % or less.

[0148] The water content of the recycled water absorbent resin composition of the present invention is preferably more than 0 mass% and not more than 20 mass%, more preferably 1 mass% or more and 15 mass% or less, even more preferably 2 mass% or more and 13 mass% or less, and particularly preferably 2 mass% or more and 10 mass% or less.

[0149] The particle size of the recycled water-absorbent resin composition of the present invention is preferably within the above range.

[0150] (7) Uses of the recycled water-absorbent resin composition The use of the recycled water absorbent resin composition obtained by the present invention is not particularly limited, but it is preferably used as an absorbent material for absorbent articles such as paper diapers, sanitary napkins, incontinence pads, etc. In particular, it can be used as an absorbent material for high-concentration paper diapers, which have been problematic in terms of odor, coloration, etc. derived from raw materials.

[0151] The present invention may also include the following inventions [1] to

[16] . [1] A method for producing a recycled water absorbent resin composition using a used water absorbent resin or a solubilized product thereof as a part or all of a raw material, (A) a drying step of a hydrogel crosslinked polymer derived from a used water absorbent resin after purification, or (B) In a manufacturing process of a recycled water-absorbent resin composition including a polymerization process of an unsaturated monomer aqueous solution, in a drying process of a hydrogel-like crosslinked polymer obtained by using a purified used water-absorbent resin or a solubilized product thereof as a part of a raw material, The above-mentioned hydrogel crosslinked polymer is subjected to azeotropic dehydration (first drying) in a hydrophobic organic solvent in the presence of a surfactant or polymer dispersant to obtain a hydrogel crosslinked polymer having a water content of 5% by mass or more and 50% by mass or less, and then filtered or evaporated to dryness to separate the hydrophobic organic solvent and the hydrogel crosslinked polymer (semi-dried gel), and further heated and dried under stirring (second drying) to obtain a dried polymer having a water content of 1% by mass or more and 20% by mass or less. [2] The method according to [1], wherein the hydrophobic organic solvent is an alkane or cycloalkane having 5 to 10 carbon atoms. [3] The method according to [1] or [2], wherein a chelating agent is further present in the drying step. [4] The method according to any one of [1] to [3], wherein the heat drying (second drying) is carried out under an air flow. [5] The method according to any one of [1] to [4], further comprising adding a reducing agent during or after the drying step. [6] The method according to any one of [1] to [5], further comprising a step of classifying the dried polymer after the drying step. [7] The method according to any one of [1] to [6], wherein the used water absorbent resin or a solubilized product thereof contains urea or ammonia. [8] The method according to any one of [1] to [7], wherein the recycled water-absorbent resin composition has a YI value of 20 or less. [9] The method according to any one of [1] to [8], wherein the recycled water absorbent resin composition has a residual monomer content of 200 ppm or less.

[10] The method according to any one of [1] to [9], further comprising a step of pulverizing the dried polymer after the drying step.

[11] A recycled water-absorbent resin composition using a used water-absorbent resin or a solubilized product thereof as a part or all of a raw material, Contains a surfactant or polymeric dispersant, Contains hydrophobic organic solvents at 1 ppm or more and 1000 ppm or less, A regenerated water-absorbent resin composition further comprising urea or ammonia.

[12] The recycled water-absorbent resin composition according to

[11] , further comprising a chelating agent.

[13] The recycled water absorbent resin composition according to

[11] or

[12] , having a moisture content of 3% by mass or more and 20% by mass or less.

[14] The recycled water-absorbing resin composition according to any one of

[11] to

[13] , further comprising a reducing agent.

[15] The recycled water-absorbent resin composition according to any one of

[11] to

[14] , which has a YI value of 20 or less.

[16] The recycled water absorbent resin composition according to any one of

[11] to

[15] , wherein a residual monomer content is 200 ppm or less. EXAMPLES

[0152] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not limited to these examples, and examples obtained by appropriately combining the technical means disclosed in each example are also included in the scope of the present invention. Unless otherwise noted, measurements were taken at room temperature (20°C or higher and 25°C or lower) and at a relative humidity of 50±5% RH. For convenience, "liter" may be expressed as "l" or "L," and "mass%" may be expressed as "wt%."

[0153] (Measurement and evaluation methods) The methods for measuring and evaluating the various physical properties in the examples and comparative examples are as follows.

[0154] (a) Water soluble content The water-soluble content of the water-absorbent resin was measured and determined by the following method.

[0155] 200.0 g of 0.90% by mass sodium chloride aqueous solution was weighed out into a 250 ml glass container containing a cylindrical rotor with a length of 35 mm and a cross-sectional diameter of 7.5 mm, and then 1.00 g of water-absorbing resin was added to the sodium chloride aqueous solution, and the container was covered with plastic wrap. After that, the aqueous solution to which the water-absorbing resin was added was stirred (rotation speed: 500 rpm) at room temperature for 16 hours using the cylindrical rotor. By this operation, the water-soluble components in the water-absorbing resin were extracted.

[0156] After stirring, the aqueous solution, which was the extract, was filtered using a sheet of filter paper (manufactured by ADVANTEC Toyo Co., Ltd., product name: JIS P3801, No. 2 / thickness 0.26 mm, retention particle size 5 μm), and 50.0 g of the resulting filtrate was used as the measurement liquid.

[0157] Next, the measurement solution was titrated with 0.1N-NaOH aqueous solution until the pH reached 10, and then titrated with 0.1N-HCl aqueous solution until the pH reached 2.7. The titration amounts at this time were calculated as [NaOH] ml and [HCl] ml, respectively.

[0158] In addition, the same procedure was carried out without adding any water-absorbent resin, using only 200.0 g of a 0.90% by mass aqueous sodium chloride solution, to determine the blank titration amount ([bNaOH] ml and [bHCl] ml).

[0159] The water-soluble content was calculated from the titer and the average molecular weight of the monomer according to the following formula (1). Water soluble content (mass%) = 0.1 × average molecular weight of monomer × 200 × 100 × ([HCl]-[bHCl]) / 1000 / 1.0 / 50.0 / (solid content concentration of water absorbent resin) / 100) Equation (1)

[0160] When the monomer average molecular weight was unknown, it was calculated using the neutralization ratio calculated by the following formula (2). Neutralization rate (mol%) = {1 - ([NaOH] - [bNaOH]) / ([HCl] - [bHCl])} × 100 Equation (2)

[0161] (b) CRC The "CRC" of a water-absorbent resin is an abbreviation for "Centrifuge Retention Capacity" and indicates the absorption capacity (unit: g / g) of a water-absorbent resin for 30 minutes under no pressure with respect to a 0.90% by mass aqueous sodium chloride solution. A specific method for measuring the CRC of a water-absorbent resin (recycled water-absorbent resin composition) is as follows.

[0162] 0.200 g of the water-absorbent resin was uniformly placed in a bag (85 mm x 60 mm) made of nonwoven fabric (manufactured by Nangoku Pulp Kogyo Co., Ltd., product name: Heatlon Paper, model: GSP-22) and heat-sealed. The bag (containing the water-absorbent resin) was immersed in a large excess (usually about 500 ml) of 0.90% by mass sodium chloride aqueous solution at room temperature. After 30 minutes, the bag was pulled out and drained for 3 minutes at a centrifugal force (250 G) described in ERT441.2-02 using a centrifuge (manufactured by Kokusan Co., Ltd., centrifuge: model H-122), and the mass W1 (g) of the bag was measured. In addition, the same operation was performed without using the water-absorbent resin, and the mass W0 (g) at that time was measured. From the obtained values ​​of W1 and W0, the CRC of the control water-absorbent resin was calculated according to the following formula (3): CRC of water-absorbent resin (g / g) = (W1-W0) / (mass of water-absorbent resin)-1···Equation (3).

[0163] (c) AAP0.3 The "AAP" of a water-absorbent resin is an abbreviation for "Absorption Against Pressure" and indicates the absorbency (unit: g / g) against a 0.90% by mass aqueous sodium chloride solution. Also, "AAP0.3" means the AAP under a pressure of 0.3 psi.

[0164] The AAP0.3 of the above water absorbent resin (regenerated water absorbent resin composition) was measured in accordance with ERT442.2-02. Specifically, 0.9 g of the water absorbent resin was placed in a large excess of 0.9 mass % sodium chloride aqueous solution for 1 hour, and the AAP0.3 was measured at 2.07 kPa (21 g / cm 2 The value was measured after swelling under a pressure of 0.5 psi (0.3 psi).

[0165] (d) Color evaluation (yellowness index / YI value) The color evaluation of the water-absorbent resin was performed using a spectrophotometer (Spectrophotometer SE7700) manufactured by Nippon Denshoku Industries Co., Ltd. Reflection measurement was selected as the measurement setting condition, and the measurement diameter was LAV (28 mm). In addition, the attached 35Φ×15H round cell, 35Φ×15H cell case, and standard white board for powder were used. The YI value (Yellow Index) was measured with the above spectrophotometer under the conditions of room temperature (20°C or higher and 25°C or lower) and humidity of 50 RH%.

[0166] (e) Residual monomer content (residual acrylic acid content) The amount of residual monomers in the water absorbent resin was quantified according to ERT410.2-02 (Residual Monomers).

[0167] Specifically, 1.0 g of the water-absorbent resin is dissolved in 200 cm of a 0.90% by mass aqueous solution of sodium chloride. 3 (temperature: 23±2° C.), stirred at 500±50 rpm for 1 hour, and then filtered. The amount of residual monomer in the obtained filtrate was measured by HPLC.

[0168] (f) Residual acrylamide content The filtrate obtained in the above (h) measurement of the amount of residual monomer was concentrated as necessary, and the content of residual acrylamide was measured by HPLC.

[0169] (g)Urea content 200.0 g of 0.9% by mass sodium chloride aqueous solution was weighed into a plastic container with a capacity of 250 ml and a lid. Next, 1.00 g of water absorbent resin was added to the sodium chloride aqueous solution, and the mixture was stirred for 16 hours by rotating a stirrer. By this operation, the urea content in the water absorbent resin was extracted.

[0170] Subsequently, the extract was filtered through a filter (0.45 μm), and the obtained filtrate was analyzed by liquid chromatography (HPLC) to quantitatively determine the amount of urea contained in the water-absorbent resin.

[0171] (g) Solid content concentration / moisture content A water-absorbent resin (hydrated gel) having a mass Wa (g) was placed on an aluminum plate having a mass Wb (g) and dried in a hot air circulating oven at 180° C. for 3 hours. Thereafter, the total mass Wc (g) of the water-absorbent resin (hydrated gel) and the aluminum plate was measured. From the obtained values ​​of Wa, Wb, and Wc, the solid content concentration of the water-absorbent resin (hydrated gel) was calculated according to the following formula (4): Solids concentration (mass%) of water-absorbent resin (hydrated gel) = {(Wc - Wb) / Wa} × 100 Equation (4).

[0172] The water content of the water-absorbent resin (hydrous gel) is calculated according to the following formula (5): Water content (mass%) of water-absorbent resin (water-containing gel) = 100 – (solids concentration of water-absorbent resin (water-containing gel)) Equation (5).

[0173] (h) Mass average molecular weight, number average molecular weight, molecular weight distribution (Preparation of measurement samples) First, the water-absorbent resin (hydrogel) was dissolved in the following solvent to obtain a solution with a concentration of 0.1% by mass. The obtained solution was then passed through a filter (GL Sciences: GL Chromatodisk, aqueous 25A, pore size 0.2 μm) to obtain a measurement sample. Solvent: Aqueous solution containing 60 mM sodium dihydrogen phosphate dihydrate, 20 mM sodium dihydrogen phosphate dodecahydrate, and 400 ppm sodium azide (pH: 6.35 to 6.38). Using the measurement sample, GPC measurement was carried out under the following measurement conditions.

[0174] (GPC measurement) The above measurement samples were subjected to GPC measurement using a Viscotec TDAmax manufactured by Malvern Instruments. The measurement device was equipped with a size exclusion chromatograph, a refractive index detector, a light scattering detector, and a capillary viscometer. The measurement device and measurement conditions were as follows. Pump, autosampler: Viscotec GPCmax (Malvern) Guard column: OHpak SB-G (Showa Denko Co., Ltd.) Column: OHpak SB-806MHQ (Showa Denko K.K.), two columns connected in series Detector: Viscotec TDAmax (Malvern) Solvent: Aqueous solution containing 60 mM sodium dihydrogen phosphate dihydrate, 20 mM sodium dihydrogen phosphate dodecahydrate, and 400 ppm sodium azide (pH: 6.35 to 6.38). Flow rate: 0.5mL / min Injection volume: 100μl.

[0175] The water used in the GPC measurements was pure water from which impurities had been thoroughly removed. The GPC measurements were performed under conditions where the detector baseline was stable, particularly when there were no noise peaks in the light scattering detector.

[0176] The measuring device was calibrated using polyoxyethylene glycol (mass average molecular weight (Mw): 21966, molecular weight distribution (Mw / Mn): 1.0, differential refractive index (dn / dc): 0.132, solvent refractive index: 1.33) as a standard sample.

[0177] In addition, the differential refractive index (dn / dc) of the water-absorbent resin to be measured was set to 0.12, and the solvent refractive index was set to 1.33. Data collection and analysis of the refractive index, light scattering intensity, and viscosity were performed using software (Viscotek OmniSEC4.7.0 (registered trademark)).

[0178] Based on the refractive index (RI), light scattering intensity (angle: 7°) (LALS) and data obtained from the viscometer (DP) obtained in the above measurements, the mass average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the water-absorbent resin (hydrous gel) were calculated.

[0179] [Production Example 1] A reaction liquid was prepared by dissolving 0.44 parts by mass of polyethylene glycol diacrylate (molecular weight: 523) in 550 parts by mass of a 38% by mass aqueous solution of sodium acrylate (neutralization rate: 71 mol%), and the reaction liquid was degassed for 30 minutes under a nitrogen gas atmosphere.

[0180] The reaction liquid was then fed to a jacketed stainless steel twin-arm kneader having two sigma-type blades with an openable lid, and the gas in the system was replaced with nitrogen gas while maintaining the liquid temperature at 30°C.

[0181] Next, while stirring the liquid in the kneader, 0.24 parts by mass of ammonium persulfate and 0.012 parts by mass of L-ascorbic acid were added to the system, and the polymerization reaction started about 1 minute later. This polymerization was carried out at 30° C. or higher and 95° C. or lower. 60 minutes after the start of polymerization, a hydrogel-like crosslinked polymer (hereinafter abbreviated as "hydrogel") (S1) was taken out of the system.

[0182] The obtained hydrogel (S1) was dried with hot air at 150° C. for 100 minutes. The dried product was then pulverized using a vibration mill. The pulverized product was then classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm. This operation yielded an irregularly pulverized water-absorbent resin precursor (S1).

[0183] A surface crosslinking agent composition liquid consisting of 0.03 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of water was added to 100 parts by mass of the obtained water absorbent resin precursor (S1), and the obtained mixture was mixed. Next, the obtained mixture was heat-treated at 100°C for 45 minutes to perform surface crosslinking of the water absorbent resin precursor (S1), thereby obtaining a water absorbent resin (S1).

[0184] The obtained water absorbent resin (S1) had a water soluble component amount of 9 mass %, a CRC of 41.7 g / g, an AAP0.3 of 30.7 g / g, and was white in color.

[0185] [Production Example 2] 20.0 g of the water absorbent resin (S1) obtained in Production Example 1 was placed in a beaker, and 600.0 g of artificial urine (a solution consisting of 1.9 mass% urea, 0.80 mass% sodium chloride, 0.10 mass% magnesium chloride hexahydrate, 0.10 mass% calcium chloride dihydrate, and 97.1 mass% ion-exchanged water) was added to the beaker. After that, the beaker was left at room temperature for 24 hours, and the obtained product was used as a simulated used water absorbent resin (S1).

[0186] Next, 1500.0 g of 2.7 mass% citric acid aqueous solution was added to the beaker containing 620.0 g of the simulated used water absorbent resin (S1) and stirred for 15 minutes (dehydration treatment). Then, the contents of the beaker were filtered through a 100 mesh (150 μm mesh) stainless steel wire mesh.

[0187] The filtrate (333.4 g) obtained after the dehydration treatment was returned to an empty beaker, and 2000.0 g of ion-exchanged water was added to the beaker and stirred for 15 minutes (water washing treatment). After that, the contents of the beaker were filtered through a 100-mesh stainless steel wire screen.

[0188] 536.5 g of the filtrate obtained by the above filtration and after the water washing treatment was placed in an empty container with a capacity of 2000 mL. Next, 64.2 g of a 10% by mass aqueous sodium hydroxide solution was dropped into the filtrate while stirring it with a spatula (neutralization treatment).

[0189] By this operation, a washed hydrogel (S1) was obtained. The obtained washed hydrogel (S1) had a content of urea derived from artificial urine of about 3 mass % (based on the solid content).

[0190] [Production Example 3] 22.4 parts by mass of sodium carbonate was added to 100 parts by mass of the washed hydrogel (S1) obtained in Production Example 2. Thereafter, the temperature of the obtained mixture was raised to 80° C. while stirring, and 6.67 parts by mass of a 30% by mass aqueous hydrogen peroxide solution was added to the system.

[0191] By this operation, the decomposition (solubilization) of the washed hydrogel (S1) was started. After heating for 3 hours from the start of the decomposition, the obtained aqueous solution of the solubilized polymer (S1) was concentrated with an evaporator to obtain a solubilized polymer concentrate (S1) having a solid content of 30.0 mass% and a molecular weight of about 200,000.

[0192] [Production Example 4] A reaction vessel was charged with 220.4 g of acrylic acid, 0.64 g (0.040 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 93.4 g of a 48.5 mass % aqueous sodium hydroxide solution, and 213.7 g of deionized water, and mixed to prepare an aqueous monomer solution (S4').

[0193] Next, the monomer aqueous solution (S4') was cooled while stirring. When the liquid temperature reached 40.0°C, 90.8 g of a 48.5% by mass aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (S4). At this time, the temperature of the monomer aqueous solution (S4) rose to 78.1°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5% by mass aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved and became a transparent homogeneous solution.

[0194] Next, 10.9 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred monomer aqueous solution (S4), and the mixture was immediately poured into a stainless steel vat-type container in an open-air system. The time from the start of the second neutralization to the pouring of the monomer aqueous solution (S4) into the vat-type container was 55 seconds, and the vat-type container was a hot plate, which was heated until the surface temperature reached 40°C after the monomer aqueous solution (S4) was poured. The polymerization reaction started 70 seconds after the monomer aqueous solution (S4) was poured into the vat-type container. The polymerization reaction proceeded while the reactants expanded and foamed in all directions while generating water vapor. After the reaction, the reactants shrunk to a size slightly larger than the vat-type container. The reactants were taken out as a hydrous gel (S4) 3 minutes after the start of the polymerization reaction. The series of operations was carried out in an open-air system.

[0195] The hydrogel (S4) obtained by the polymerization reaction was cut into strips and crushed with a meat chopper having a die diameter of 7.5 mm to obtain a particulate hydrogel (S4).

[0196] [Production Example 5] In Production Example 4, the same procedure as in Production Example 4 was carried out, except that 100.0 g of the solubilized polymer concentrate (S1) obtained in Production Example 3 and 113.6 g of deionized water were used instead of 213.7 g of deionized water when preparing the aqueous monomer solution (S4'), to obtain a particulate hydrogel (S5) (solid concentration: approximately 50% by mass).

[0197] [Example 1] 1.0 L of n-heptane was placed in a 2 L four-necked separable flask (see FIG. 1) equipped with a stirrer, a reflux condenser, a thermometer, a nitrogen gas inlet tube, and a dropping funnel, and 3.8 g of a sucrose fatty acid ester (Dai-ichi Kogyo Yakuhin Co., Ltd., DK-Ester F-50, HLB=6) was added as a surfactant and dissolved.

[0198] Next, 300 g of the particulate hydrous gel (S5) obtained in Production Example 5 was added to the separable flask. Then, the flask contents were immersed in an oil bath at 100° C. while being stirred at 170 rpm, and azeotropic dehydration (first drying) was started. The azeotropic dehydration was continued until the water content of the particulate hydrous gel (S5) reached 15% by mass. Then, n-heptane (boiling point 98° C.) was evaporated to dryness to obtain a hydrous gel (1) having a water content of 15% by mass.

[0199] Next, the separable flask containing the hydrous gel (1) was immersed in an oil bath at 150° C. while stirring the contents of the flask at 170 rpm, and stirring and drying (second drying) was started. The stirring and drying was continued until the water content of the hydrous gel (1) reached 5% by mass.

[0200] Thereafter, the dried polymer obtained by the above drying was pulverized and classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain a recycled water-absorbent resin composition (1). The physical properties of the recycled water-absorbent resin composition (1) are shown in Table 1.

[0201] [Comparative Example 1] The same operation as in Example 1 was carried out except that the drying of the particulate hydrogel (S5) was changed to static hot air drying (drying temperature: 180°C, drying time: 1 hour) in Example 1, to obtain a recycled water absorbent resin composition (C1). The physical properties of the recycled water absorbent resin composition (C1) are shown in Table 1.

[0202] [Comparative Example 2] The same operation as in Example 1 was carried out except that the stirring drying (second drying) was continued until the moisture content of the particulate hydrogel (S5) reached 0.5 mass%, to obtain a recycled water absorbent resin composition (C2). The physical properties of the recycled water absorbent resin composition (C2) are shown in Table 1.

[0203] [Comparative Example 3] In Example 1, drying (azeotropic dehydration (first drying)) of the particulate hydrogel (S5) was started without using a surfactant. During the azeotropic dehydration, the particulate hydrogel aggregated, and drying could not be continued.

[0204] [Example 2] A recycled water-absorbent resin composition (2) was obtained by the same procedure as in Example 1, except that 0.5% by mass of sodium sulfite, a reducing agent, was added to the particulate hydrogel (S5). The physical properties of the recycled water-absorbent resin composition (2) are shown in Table 1.

[0205] [Example 3] The same procedure as in Example 1 was carried out except that 0.1% by mass of diethylenetriamine pentaacetate sodium, a chelating agent, was added to the particulate hydrogel (S5) to obtain a recycled water-absorbent resin composition (3). The physical properties of the recycled water-absorbent resin composition (3) are shown in Table 1.

[0206] [Reference example 1] A recycled water absorbent resin composition (Reference 1) was obtained by carrying out the same operation as in Comparative Example 1, except that the particulate hydrogel (S5) in Comparative Example 1 was changed to the particulate hydrogel (S4) obtained in Production Example 4. The recycled water absorbent resin composition (Reference 1) was white without any coloring. It can be seen from Reference Example 1 that the coloring after drying originates from the used water absorbent resin used as a raw material. The physical properties of the recycled water absorbent resin composition (Reference 1) are shown in Table 1.

[0207] [Table 1]

[0208] [Production Example 6] The washed hydrogel (S1) obtained in Production Example 2 was further subjected to a dehydration treatment at room temperature to obtain a washed hydrogel (S6) having a swelling ratio of 3 times (solid content of about 35% by mass).

[0209] [Example 4] 1.0 L of n-heptane was placed in a 2 L four-necked separable flask (see FIG. 1) equipped with a stirrer, a reflux condenser, a thermometer, a nitrogen gas inlet tube, and a dropping funnel, and 3.8 g of a sucrose fatty acid ester (Dai-ichi Kogyo Yakuhin Co., Ltd., DK-Ester F-50, HLB=6) was added as a surfactant and dissolved.

[0210] Next, 300 g of the washed hydrous gel (S6) obtained in Production Example 6 was added to the separable flask. Then, the flask content was immersed in an oil bath at 100° C. while stirring at 170 rpm, and azeotropic dehydration (first drying) was started. The azeotropic dehydration was continued until the water content of the washed hydrous gel (S6) became 15% by mass. Then, n-heptane was evaporated to dryness to obtain a hydrous gel (4) having a water content of 15% by mass.

[0211] Next, the separable flask containing the hydrous gel (4) was immersed in an oil bath at 150° C. while stirring the contents of the flask at 170 rpm, and stirring and drying (second drying) was started. The stirring and drying was continued until the water content of the hydrous gel (4) reached 5% by mass.

[0212] Thereafter, the dried polymer obtained by the above drying was pulverized and classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain a recycled water-absorbent resin composition (4). The physical properties of the recycled water-absorbent resin composition (4) are shown in Table 2.

[0213] [Comparative Example 4] In Example 4, azeotropic dehydration (first drying) was performed until the water content of the washed hydrogel (S6) reached 5% by mass, and then n-heptane was evaporated to dryness and separated, but the same procedure as in Example 4 was performed to obtain a recycled water absorbent resin composition (C4). The obtained recycled water absorbent resin composition (C4) had a slight solvent odor (n-heptane odor). The physical properties of the recycled water absorbent resin composition (C4) are shown in Table 2.

[0214] [Comparative Example 5] In Example 4, drying (azeotropic dehydration (first drying)) of the washed hydrogel (S6) was started without using a surfactant. During the azeotropic dehydration, the washed hydrogel (S6) aggregated, and drying could not be continued.

[0215] [Comparative Example 6] The same procedure as in Example 4 was carried out except that the drying of the washed hydrogel (S6) was changed to static hot air drying (drying temperature: 180°C, drying time: 1 hour) to obtain a recycled water absorbent resin composition (C6). The physical properties of the recycled water absorbent resin composition (C6) are shown in Table 2.

[0216] [Comparative Example 7] A recycled water absorbent resin composition (C7) was obtained by the same procedure as in Comparative Example 6, except that 0.5% by mass (based on solid content) of hydrogen peroxide, which is a bleaching agent, was added to the washed hydrogel (S6) before drying. The physical properties of the recycled water absorbent resin composition (C7) are shown in Table 2.

[0217] [Comparative Example 8] A recycled water absorbent resin composition (C8) was obtained by the same procedure as in Comparative Example 6, except that 3% by mass (based on solid content) of hydrogen peroxide, which is a bleaching agent, was added to the washed hydrogel (S6) before drying. The physical properties of the recycled water absorbent resin composition (C8) are shown in Table 2.

[0218] [Example 5] A recycled water absorbent resin composition (5) was obtained by the same procedure as in Example 4, except that 0.1% by mass of sodium sulfite as a reducing agent was added to the washed hydrogel (S6) before drying. The physical properties of the recycled water absorbent resin composition (5) are shown in Table 2.

[0219] [Example 6] A recycled water absorbent resin composition (6) was obtained by the same procedure as in Example 4, except that 0.1% by mass of diethylenetriamine sodium pentaacetate, a chelating agent, was added to the washed hydrogel (S62) before drying. The physical properties of the recycled water absorbent resin composition (6) are shown in Table 2.

[0220] [Table 2]

[0221] (summary) From Tables 1 and 2, it can be seen that azeotropic dehydration (first drying) is carried out in a hydrophobic organic solvent in the presence of a surfactant or polymer dispersant to obtain a hydrogel having a water content of 5% by mass or more and 50% by mass or less, the hydrophobic organic solvent is then filtered or evaporated to dryness to separate it from the hydrogel, and further heat-dried under stirring (second drying) to obtain a dried polymer having a water content of 1% by mass or more and 20% by mass or less, thereby reducing coloration and residual monomers and suppressing the by-production of acrylamide, which is specific to recycled water absorbent resin compositions.

[0222] Furthermore, it is clear from Examples 2, 3, 5, and 6 that the addition of specific additives (reducing agents, chelating agents) in the drying process can further reduce coloration and residual monomers.

[0223] Although not shown in the table, the recycled water absorbent resin compositions obtained in the examples contain urea, a surfactant, 1000 ppm or less of a hydrophobic organic solvent, and 5 mass % of water, and can be suitably recycled. [Industrial Applicability]

[0224] The method of the present invention provides a method for obtaining a regenerated water absorbent resin with less foreign matter, coloration, and residual monomers and with less deterioration, from a used water absorbent resin, without excessively consuming resources in recycling, and therefore contributes to the environment and resource saving and expands the possibility of recycling the water absorbent resin.

Claims

1. A method for producing a recycled water absorbent resin composition using a used water absorbent resin or a solubilized product thereof as a part or all of a raw material, comprising: (A) a drying step of a hydrogel crosslinked polymer derived from a used water absorbent resin after purification, or (B) In a manufacturing process of a recycled water-absorbent resin composition including a polymerization process of an unsaturated monomer aqueous solution, in a drying process of a hydrogel-like crosslinked polymer obtained by using a purified used water-absorbent resin or a solubilized product thereof as a part of a raw material, The above-mentioned hydrogel crosslinked polymer is subjected to azeotropic dehydration (first drying) in a hydrophobic organic solvent in the presence of a surfactant or a polymer dispersant to obtain a hydrogel crosslinked polymer having a water content of 5% by mass or more and 50% by mass or less, and then the hydrophobic organic solvent and the hydrogel crosslinked polymer (semi-dried gel) are separated by filtration or evaporation to dryness, and the hydrophobic organic solvent and the hydrogel crosslinked polymer (semi-dried gel) are separated by heating and drying under stirring (second drying) to obtain a dried polymer having a water content of 1% by mass or more and 20% by mass or less.

2. The method according to claim 1 , wherein the hydrophobic organic solvent is an alkane or cycloalkane having from 5 to 10 carbon atoms.

3. The method of claim 1 , further comprising the presence of a chelating agent in the drying step.

4. The method according to claim 1 , wherein the heat drying (second drying) is carried out under air flow.

5. The method of claim 1 , further comprising adding a reducing agent during or after the drying step.

6. The method according to claim 1, further comprising a step of classifying the dried polymer after the drying step.

7. The method according to claim 1 , wherein the used water absorbent resin or a solubilized product thereof contains urea or ammonia.

8. The method according to claim 1, wherein the recycled water absorbent resin composition has a YI value of 20 or less.

9. The method according to claim 1, wherein the recycled water absorbent resin composition has a residual monomer content of 200 ppm or less.

10. The method of claim 6, further comprising the step of grinding the dried polymer after the drying step.

11. A recycled water-absorbent resin composition using a used water-absorbent resin or a solubilized product thereof as a part or all of a raw material, Contains a surfactant or polymeric dispersant, Contains a hydrophobic organic solvent in an amount of 1 ppm or more and 1000 ppm or less, A regenerated water-absorbent resin composition further comprising urea or ammonia.

12. The recycled water-absorbent resin composition according to claim 11, further comprising a chelating agent.

13. The recycled water absorbent resin composition according to claim 11, having a moisture content of 3% by mass or more and 20% by mass or less.

14. The recycled water-absorbent resin composition according to claim 11, further comprising a reducing agent.

15. The recycled water-absorbent resin composition according to claim 11, having a YI value of 20 or less.

16. The recycled water-absorbent resin composition according to claim 11, wherein the residual monomer content is 200 ppm or less.

Citation Information

Patent Citations

  • Method and system for recovering pulp fibers and highly water-absorbent polymer from used absorbent articles

    WO2019087485A1

  • Method for regenerating highly water-absorbing polymer, method for producing highly water-absorbing recycled polymer, and use of alkali metal ion source

    WO2019151538A1

  • Method for producing water-absorbing resin particles

    WO2020213298A1

  • Method for recycling superabsorbent polymer derived from used absorbent article and recycled superabsorbent polymer derived from used absorbent article

    WO2020241025A1

  • Method for producing recycled superabsorbent polymer, method for producing superabsorbent polymer using recycled superabsorbent polymer, and recycled superabsorbent polymer

    WO2021044690A1